Psychological Well Being and Quality of Sleep Among Health Care Professionals at Tertiary Care Hospital - Pradhan, Nikita; Ojha, Saroj Prasad; Shakya, Suraj; Pradhan, Pramesh Man (Journal of Institute of Medicine Nepal, 2025)
Introduction Psychological well-being is linked to positive life outcomes and quality of sleep. Healthcare professionals often experience inconsistent sleep, affecting their well-being and patient care. This study aims to explore psychological well-being and quality of sleep of healthcare professionals and the association between them. Methods A cross-sectional descriptive study was conducted among 305 health care professionals (medical doctors=61, nurses=183, laboratory technicians=61) selected by purposive sampling. A pre-structured questionnaire including socio-demographics, Ryff’s Psychological Well-being (PWB) scale and The Pittsburgh Sleep Quality Index (PSQI) were used. The result has been expressed using descriptive and inferential statistics. Pearson Correlation was used to find relationship between psychological well-being and quality of sleep. Results The mean age of participants was 35.01±3.67 years with female preponderance of 248 (81.3%). PWB differed significantly across professions (p=0.01). Low PWB was reported by 23(37.7%) laboratory technicians, followed by 38(20.8%) nurses and 20(32.8%) medical doctors. Overall, 35.10% of participants experienced poor quality of sleep including, 19(31.1%) medical doctors, 72(39.3%) nurses and 16(26.2%) laboratory technicians. Quality of sleep was not significantly associated with gender and type of profession. A weak negative correlation between PWB and PSQI scores (r=−0.32), indicating that higher PWB was associated with lower PSQI scores, and thus good sleep quality. Conclusion Psychological well-being and quality of sleep demonstrated considerable variation among healthcare professionals. Improving quality of sleep will be an effective strategy to decrease the risk of developing lover psychological well-being among healthcare professionals.